Multicultural learning based on blended learning in social studies and the impact on nationalism attitude viewed from students’ cultural literacy level - Setemen, Komang; Widiana, I Wayan; Antara, I Gede Wahyu Suwela (Nurture, 2023)
Purpose: This study aimed at analyzing the impact of blended multicultural learning on nationalism as seen from the students’ cultural literacy level in social studies learning. Design/Methodology/Approach: This is quasi-experimental research with a non-equivalent post-test-only control group design. The research was conducted with a population of 212 V grades in elementary school. The technique used was random sampling. Based on the random sampling, the sample obtained was 64 students divided into two classes. The 32 students were put in the experimental group, and the other 32 were put in the control group. The data collection used tests and questionnaires. This study used descriptive and inferential analysis methods. Inferential analysis was carried out using Two-Way Analysis of Variance, which was preceded by an analysis prerequisite test that included a test for normality of data distribution and a test for homogeneity of variance. Findings: Based on the results of the data analysis, it was found that the blended multicultural learning approach and the level of cultural literacy had a positive impact on social studies learning. Conclusion: It was concluded that the blended multicultural learning approach and the level of cultural literacy can contribute to influencing the attitude of nationalism in elementary school students. Practical Implication: It is expected that teachers can apply a blended multicultural learning approach and pay attention to the level of student cultural literacy so that it can increase students' nationalist attitudes.